Synergistic Effects of Bleomycin and Hypericum Triquetrifolium Extract on Bone Marrow and Germ Cells of Albino Mice - Bushra Mohammed Amin Mohammed (Journal of Global Pharma Technology, 2018)
The aim of this study was to explore the cytogenetic effects of Bleomycin (BLM) and the aqueous extract of Hypericum triqutrifolium  each alone and their interaction (pre-treatment, post-treatment, co-treatment) on bone marrow and germ cells of Swiss albino mice depending on  Chromosome aberration assay, Micronuclei test , Mitotic index assay in addition to sperm abnormal morphology assay .The result showed  that the administration of a single dose of Bleomycin (80mg/kg) and of H. triqutrifolium (17mg/kg) each alone, for three consecutive days  have the ability to increase the total abnormal chromosomes, total micro nucleated cells and reduce the percentage of mitotic index value in bone marrow cells, in addition to enhancing the total number of abnormal spermatozoa .While their interaction revealed that the co-treatment (the mixture of Bleomycin and H. triqutrifolium ) amplify  significantly the total aberrant chromosomes  ,the most frequent types were ;chromatid break with fragment, ring chromosome, dysenteric chromosome , and  chromatid gap. Similar reduction in the percentage of cell proliferation but with a non-significant value was observed in pre, post and co-treatment.  Moreover the co-administration had increased the total number of micro nucleated cells and enhances significantly the frequency of abnormal sperm cells such as bent mid piece, irregular head, coiled tail and corkscrew types compared with the treated and untreated animals. Overall, those results herein found suggest an herb-drug interaction between H. triqutrifolium extract and Bleomycin, which clearly increase the drug bioavailability, with the lowest acute cytotoxicity .To reliably assess the clinical impact of these findings appropriate human studies should be conducted.Keywords: Bleomycin, Chromosome aberration, H.triqutrifolium, Micronuclei test, Mitotic index sperm abnormalities.